精英同学会 ：新加坡“海燕等人”剧团研究 (1991-2014) = The elite's journey : a study on the ETCeteras (1991-2014) - 廖慧婷 Liao, Huiting (2015)
1990年代，包括“海燕等人”在内，有多达12个新华语剧团在本地诞生。而“海燕等人”剧团更是少数在这20多年来依然活跃的华语剧团之一。集合出身自华初校友的海燕等人，是本地剧团中少见由多位专业人士和精英分子构成的业余华语剧团。剧团的特色在于反映现实，其作品反映了出生于70年一代的生活心态和社会关心。从早期对于政策的讽刺到后期对人生的反思，无一不反映他们的生活轨迹。此外，核心成员们的经历和背景赋予他们作品在新加坡华语剧场中具有特别含义。本文将在介绍剧团的成立和发展的同时，点出剧团和成员的独特之处。随后分析剧团的作品与国家之间的关系，以及剧团走向的转变所象征的意义。为此，笔者将结合某些剧团核心成员的个人背景与剧团的走向与作品进行分析。最后，本文也将结合本地社会和政治背景以及相关本地报章报道作为分析海燕等人剧团和其剧作的主要手段。During 1990s, there are 12 newly founded Singapore Chinese theatre troupes including The ETCeteras. The ETCeteras is also one of those rare ones who are still active in these past 20 over years. Members formed by the Hwa Chong Junior College’s alumni, The ETCeteras is led by a team of elites and professionals. Their productions are said to represent much of the lives and concerns similar from those who are born in the 70s. The ETCeteras’ productions also reflects upon the reality and social concerns, from their earlier productions which daringly criticizes public policy to the latter shows reflecting upon life. The leading member’s unique personal background also gives their shows special meaning to the local theatre. This thesis will firstly introduce the history of The ETCeteras and some important pointers about their founding members. Next, I will analyse some of their works hoping to point out some meanings between them and the relationship with the nation, including the significance of their changes in their latter stage. To achieve this goal, I will combine some background information of the leading members, together with the progression of the troupe when analysing their work. Lastly, I will also include local society and politics background information, including various local news articles to support my point of view.